Racial/Ethnic Disparities in the Incidence of Epithelial Ovarian Cancer in Florida by Histology, 2001–2015: Analysis of Trends. Issue 7 (July 2021) - Westrick, Ashly; Schlumbrecht, Matthew; Pinheiro, Paulo; Hlaing, WayWay; Kobetz, Erin; Feaster, Daniel; Balise, Raymond
Abstract : Objectives: Because the population in Florida is 25.6% Hispanic, it is possible to evaluate the influence of race and ethnicity within clinically relevant subgroups of women with epithelial ovarian cancer (EOC), including histology and tumor grade. This study explores racial/ethnic disparities in the incidence of EOC in Florida by histology and tumor grade. Methods: This study is an analysis of the Florida Cancer Database System. All incidence EOC cases from 2001 through 2015 were identified. Age-adjusted incidences were calculated and trends modeled by race/ethnicity and histology using Joinpoint and Poisson regression. Results: In total, 80% of the 21, 731 women with EOC were White, followed by Hispanic (13.1%) and non-Hispanic Black (7.9%). All races/ethnicities had statistically significant declines in incidence, with non-Hispanic White and non-Hispanic Black women having the steepest declines (annual percentage change −2.5, 95% confidence interval [CI] −5.9 to −2.1 and annual percentage change −2.8, 95% CI −4.8 to −1.5, respectively). A decreased incidence trend across the time period was seen for all subgroups (relative risk 0.97 [95% CI 0.96–0.98], 0.96 [95% CI 0.96–0.99], and 0.98 [95% CI 0.96–0.99] for non-Hispanic White, non-Hispanic Black, and Hispanic). High-grade EOC incidence for all groups did not change with time. Conclusions: We found significant declines in the incidence of EOC for all races/ethnicities, but not for high-grade EOC. The observed incidence decline in Hispanic women differs from previous research. More research is needed to understand women the causes of overall racial/ethnic differences and the decline in EOC. Abstract : Ovarian cancer incidence has been decreasing in recent decades, with persistent racial/ethnic disparities. Many previous studies have focused on non-Hispanic White and non-Hispanic Black women with relatively fewer including Hispanic women. Florida presents a unique opportunity to evaluate racial/ethnic disparities in health. This article provides an analysis of ovarian cancer incidence trends by race/ethnicity and histology in Florida from 2001 to 2015.